2018
DOI: 10.1002/chem.201801639
|View full text |Cite
|
Sign up to set email alerts
|

Anion–π Interaction‐Induced Room‐Temperature Phosphorescence of a Polyoxometalate‐Based Charge‐Transfer Hybrid Material

Abstract: Room-temperature phosphorescence (RTP) was realized for the first time in a polyoxometalate-based charge-transfer (CT) hybrid material bearing polyoxometalates (POMs) as electron-donors (D) and rigid naphthalene diimides (NDIs) as electron-acceptors (A), meanwhile, this hybrid material displayed photochromism as well. The significant D-A anion-π interaction induced an additional through-space charge-transfer pathway. The resulting suitable D-A CT states can efficiently bridge the relatively large energy gap be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 63 publications
2
34
2
Order By: Relevance
“…16 In recent years, Lu and our groups have reported that many hybrid crystal materials are composed of NDIs and POMs via anion-π interactions, which not only possess photochromic behavior but also present room temperature phosphorescence. 10,11,16 Although organic components are an important part of hybrid materials, there are still a few studies that explore the difference of the above two properties by modifying organic moieties. Based on previous research, chemical modification at core positions of NDIs (c-NDI) can notably tune the properties through introducing the substitution of electron withdrawing groups or electron donating groups at core positions, like alkyl, cyano, etc.…”
Section: ■ Introductionmentioning
confidence: 99%
“…16 In recent years, Lu and our groups have reported that many hybrid crystal materials are composed of NDIs and POMs via anion-π interactions, which not only possess photochromic behavior but also present room temperature phosphorescence. 10,11,16 Although organic components are an important part of hybrid materials, there are still a few studies that explore the difference of the above two properties by modifying organic moieties. Based on previous research, chemical modification at core positions of NDIs (c-NDI) can notably tune the properties through introducing the substitution of electron withdrawing groups or electron donating groups at core positions, like alkyl, cyano, etc.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The X‐ray resolved structures of polyoxometalates at transient times should be investigated since the charge transfer process underpinning the energy device performance happens at micron‐, nano‐, pico‐, or even femto‐second scale. Time‐resolved crystallography and photocrystallography have been found especially pertinent to grasp the transient behavior of metal complexes and could be carried out to understand the structures of polyoxometalates at different timescales …”
Section: Suggestions and Outlookmentioning
confidence: 99%
“…The resulting quadrupole moment decides whether an anion tends to locate in the space above the ring (positive, π-acidic surface) or instead in more distant peripheral regions closer to the ring plane (negative, electron-poor edge). Thus, canonical anion-π synthons reveal their significance in performance of advanced small-molecule catalytic systems dedicated to specific organic reactions, [1][2][3] photophysical systems based on charge or electron transfer properties, [4][5][6][7][8][9] anion recognition, binding, and sensing, [10][11][12][13] anion transport, [14][15][16][17] or anion directed self-assembly of polynuclear coordination complexes. 18 Further on, the new generation supramolecular and coordination anion-π architectures hosting mononuclear 8,[19][20][21] and polynuclear d-metalate complexes 9,22,23 were recently reported in the context of anion binding, 19,20 molecular crystalline composites, 21 charge transfer and photophysical properties, 8,9,[20][21][22] or magnetic properties.…”
Section: Introductionmentioning
confidence: 99%